A multicenter open-label phase II trial to evaluate nivolumab and ipilimumab for 2nd line therapy in elderly patients with advanced esophageal squamous cell cancer (RAMONA) - Meindl-Beinker, Nadja M.; Betge, Johannes; Gutting, Tobias; Burgermeister, Elke; Belle, Sebastian; Zhan, Tianzuo; Schulte, Nadine; Ebert, Matthias; Härtel, Nicolai (BMC cancer, 2019)
Advanced esophageal squamous cell cancer (ESCC) is frequently diagnosed in elderly patients. The impact of 2nd line chemotherapy is poorly defined. Recent data demonstrated effectiveness of checkpoint inhibitors in different squamous cell carcinomas. Therefore, we assess combined nivolumab/ipilimumab as 2nd line therapy in elderly ESCC patients.
Gesehen am 10.04.2019